Potente P2Y12-Rezeptorhemmer bei Patienten mit akutem Koronarsyndrom - Sibbing, D.; Orban, M.; Massberg, S. (Hämostaseologie, 2013)
Blood platelets are highly activated in the setting of an acute coronary syndrome (ACS). This fact mandates the need for potent platelet inhibition in ACS patients and especially in patients undergoing a percutaneous coronary intervention (PCI). The 2nd generation thienopyridine clopidogrel has been the standard of treatment in the past. Due to its pharmacological properties including a delayed onset of action, a large response variability and an insufficient antiplatelet action in some patients (low responsiveness or high on-treatment platelet reactivity), there was a need to develop, to study and to introduce more potent agents with a fast, reliable and potent antiplatelet action. With the 3rd generation thienopyridine prasugrel and with ticagrelor two potent agents for antiplatelet treatment of ACS patients are available now. Both drugs have demonstrated their superiority compared to clopidogrel in terms of thrombotic risk reduction in large-scale randomized trials. However, for these agents and in line with the expectations towards a more potent anti platelet treatment regimen, a higher risk for bleeding was observed for prasugrel and ticagrelor. Further on, the new anti platelet agents have their own and characteristic contraindications and numerous issues to be considered in clinical practice.This review aims to provide an overview on the state of the art P2Y12 receptor directed inhibition in ACS patients with a focus on patients undergoing a coronary stenting procedure.
Keywords: Prasugrel; ticagrelor; clopidogrel; acute coronary syndrome